Chapter 12 – In conclusion: how to manage fisheries? - Santos, Jorge (Septentrio Educational, 2015)
QUESTIONS ASKED What is the real state of fisheries around the world? What experiences have we on the assessment and management of different fish populations? When should we invest, or refrain from investing or intervening, in the fishing industry?